Investigation on thermal energy aware routing in integrated network for efficient energy storage. (2022) - Syed Jamaesha, S.; Gowtham, M.S.; Gopinath, S.; Shenbagharaman, A.; Vinoth Kumar, K.
Abstract: Mobile Ad hoc Network is one of most efficient and emergency networks where we can apply it for both commercial and domestic applications. It consists of mobile nodes where it transmits the packets without any administrator. Due to mobility, paths may be broken and attackers in the network may discover the unreliable routes to misroute the packets. In this research, a Dynamic Efficient Energy Load based Multi-hop Protocol (DEELMHP) is introduced for reliable path selection. In first phase, cluster region is formed and reliable node selection is done. In second phase, reliable routes are obtained based on packet delivery rate and path reliability cost metric. In third phase, both localization and data transmission phase was implemented to locate efficient node for packet transmission which is nearer to the destination node. The proposed protocol is evaluated and outperforms with parameters like packet delivery rate (25–86 pkts/sec), end to end delay (5.9–11.9 msec), throughput (58–21 pkts) and packet loss rate (4–21 pkts/sec).